2016
DOI: 10.1101/lm.039909.115
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdala projections to ventral hippocampus modulate the consolidation of footshock, but not contextual, learning in rats

Abstract: The basolateral amygdala (BLA) modulates memory consolidation for a variety of types of learning, whereas other brain regions play more selective roles in specific kinds of learning suggesting a role for differential consolidation via distinct BLA pathways. The ventral hippocampus (VH), an efferent target of the BLA, has been suggested to selectively process emotionrelated learning, yet whether the BLA VH pathway modulates memory consolidation, and does so in a learning-specific manner, is unknown. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 69 publications
4
53
0
Order By: Relevance
“…The nature of the interactions between the amygdala and hippocampus may consequently vary in different sub-parts of these structures and underlie different functions. In line with this notion, Huff, Emmons, Narayanan, & LaLumiere [68] have shown that the basolateral amygdala interacts with the ventral hippocampus to modulate specific types of learning (e.g., footshock learning) but not others (here context learning). This is also suggests that similarly, the hippocampus may not be one entity (e.g., [36,53,85,101]).…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 83%
“…The nature of the interactions between the amygdala and hippocampus may consequently vary in different sub-parts of these structures and underlie different functions. In line with this notion, Huff, Emmons, Narayanan, & LaLumiere [68] have shown that the basolateral amygdala interacts with the ventral hippocampus to modulate specific types of learning (e.g., footshock learning) but not others (here context learning). This is also suggests that similarly, the hippocampus may not be one entity (e.g., [36,53,85,101]).…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 83%
“…This SSFO-mediated current has been suggested to enhance activity in a structure without directly driving action potential patterns (Liu et al 2016; Yizhar et al 2011a; Yizhar et al 2011b). This represents a significant advantage over the use of traditional ChR2 constructs, which require the identification of stimulation parameters to drive neuronal activity in behaviorally relevant ways, a process that can necessitate a large number of experiments and varies depending on brain region or behavior under study (Huff et al 2016; Huff et al 2013). SSFOs also represent an advantage over DREADD approaches, as SSFOs can be activated with one wavelength of light, and deactivated with another, increasing temporal control over the manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of these projections following contextual training had no effect upon fear memory; however, activation following foot-shock enhanced fear learning. This suggests that afferents from BLA to vHPC may be primarily involved in encoding aversive, but not contextual elements of fear conditioning 65 .…”
Section: Optogenetic Tracing Of Fear Circuitrymentioning
confidence: 95%
“…Additional evidence that target specific projections from the BLA may play a role in the consolidation of select types of memory comes from Huff et al (2016). The authors activated or inhibited projections from the BLA to the vHPC during a modified contextual freezing conditioning task so as to determine whether these projections are necessary for encoding context or foot-shock memory.…”
Section: Optogenetic Tracing Of Fear Circuitrymentioning
confidence: 99%